2018
DOI: 10.1080/10826084.2018.1429472
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Gender Roles and the Stress–Alcohol Relationship among Latina/o College Students

Abstract: Background Latina/o college students have been shown to engage in more high risk drinking behavior than students from other ethnic minority groups, and are more likely to experience certain negative alcohol related consequences as a result of drinking. Previous research links stress to drinking among college students and indicates drinking occurs within a gendered context. Although this suggests an effect of gender role socialization, studies exploring these relationships among Latina/os are lacking. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…16 Items are rated on a 7-point scale (1=strongly disagree) and the means were calculated within each traditional machismo (M=2.96, SD = 1.25) and caballerismo subscale (M=6.23, SD = 0.66). Originally developed with a heterogeneous sample of Latino adult men, this scale has also been found to be reliable in Latino college samples and demonstrated excellent reliability in the present sample (traditional machismo α = 0.91; caballerismo α = 0.90) 18 .…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…16 Items are rated on a 7-point scale (1=strongly disagree) and the means were calculated within each traditional machismo (M=2.96, SD = 1.25) and caballerismo subscale (M=6.23, SD = 0.66). Originally developed with a heterogeneous sample of Latino adult men, this scale has also been found to be reliable in Latino college samples and demonstrated excellent reliability in the present sample (traditional machismo α = 0.91; caballerismo α = 0.90) 18 .…”
Section: Methodsmentioning
confidence: 62%
“…17 Research examining machismo as a bidimensional construct in relation to risky sex among Latino college men is lacking; however, research on other risky behaviors (eg, binge drinking) in this population has shown a positive association for traditional machismo but a negative one for caballerismo. 18 In response, this study examined the separate relations of traditional machismo and caballerismo to risky sexual cognitions and behaviors. Although these analyses are largely exploratory, we tentatively advanced the following hypotheses given theoretical conceptualizations of masculinity: In general, we expected traditional machismo to be positively related to cognitions promoting risky sexual behavior, and risky sexual behavior itself, while expecting the reverse to be true for caballerismo.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ACEs may also represent a key incongruent stressor as its effects on emotion regulation may directly contradict traditional machismo beliefs regarding stoicism and that displays of emotion are indications of weakness. While research has yet to examine the interactive effects of ACEs and traditional machismo on mental health, related research among Latino populations has demonstrated that other male gender role values associated with stoicism, namely caballerismo, may enhance the effect general emotional distress on alcohol use (Perrotte et al, 2018). Other work has suggested that men who endorse traditional machismo may attempt to cope with stress by restricting their emotions to conform to the masculinity ideal, which may in turn lead to an exacerbation of symptoms (Asnaani & Hall-Clark, 2017).…”
Section: Machismo and Gender Role Strain: The Importance Of Stressor mentioning
confidence: 99%
“…In contrast, traditional machismo is often examined as a risk factor where it directly predicts adverse mental health outcomes such as higher posttraumatic stress symptoms, depression, anxiety, antisocial behavior, and perceived levels of general stress (Fragoso & Kashubeck, 2000;Nunez et al, 2016). However, not all studies have found that traditional machismo has an adverse effect on mental health among Latinos (Perrotte et al, 2018).…”
mentioning
confidence: 99%
“…College student women who report depressive symptoms are more likely to also report heavy episodic drinking (HED) (Kenney, Abar, O'Brien, Clark, & LaBrie, 2016). The quantity of alcohol women consumed in one college setting appeared to be related to stress in one study (Perrotte, Baumann, & Knight, 2018). Clinical interventions have been found to break the link between HED and depressive symptoms among college students (Villarosa, Messer, Madson, & Zeigler‐Hill, 2018).…”
Section: General Strain Theorymentioning
confidence: 99%